Electrolyte powder, sheet, electrochemical element, and electricity storage device
By using garnet crystal structures of Li, Zr and La in electrolyte powder and combining electrolyte powders with Mg and Sr elements, quality management is simplified, the problem of complexity of gas adsorption method in the prior art is solved, and electricity is improved Performance and stability of chemical components.
Patent Information
- Application Number
- CN202380038752.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-10
- Filing Date
- 2023-04-25
- Publication Date
- 2024-12-17
AI Technical Summary
The specific surface area determined by the gas adsorption method in the prior art is complex and difficult to simplify the quality management index of electrolyte powder.
Electrolyte powder with a garnet crystal structure containing Li, Zr and La is used, in the CIE 1976L*a*b* color space, b*≥2, a*≥0, 2≤c*≤10 and 80≤L Within the color coordinate range of *≤97, electrolyte powder combining Mg and Sr elements is used for the manufacturing of electrochemical components and power storage devices, simplifying quality management.
Through this method, the quality management of electrolyte powder, sheet, electrochemical components and power storage devices is simplified, the ion conductivity and bondability of electrolyte powder is improved, the risk of impurities is reduced, and the operation stability of electrochemical components is enhanced .
Smart Images

Figure CN119156675A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electrolyte powder having a garnet-type crystal structure containing Li, Zr and La, a sheet containing the electrolyte powder, an electrochemical element and a power storage device. Background Art
[0002] As described in Patent Document 1, electrolyte powder having a garnet crystal structure containing Li, Zr and La is one of the materials constituting sheets and electrochemical elements. As described in Patent Document 2, the specific surface area determined by a gas adsorption method is one of the indicators for quality management of electrolyte powder.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2016-40767
[0006] Patent Document 2: Japanese Patent Application Publication No. 2021-93308 Summary of the invention
[0007] Problems to be solved by the invention
[0008] It is complicated to perform quality control using the specific surface area obtained by the gas adsorption method as an indicator.
[0009] The present invention has been made to solve the above problems, and an object of the present invention is to provide an electrolyte powder, a sheet, an electrochemical element, and a power storage device that can simplify quality management.
[0010] Means for solving problems
[0011] A first means for achieving the object is an electrolyte powder having a garnet-type crystal structure containing Li, Zr, and La, wherein b*≥2 in the color coordinates of the CIE 1976 L*a*b* color space.
[0012] For the second method, in the first method, a * ≥0.
[0013] For the third method, in the first method or the second method, c * ={(a * ) 2 +(b * ) 2} 1 / 2 The saturation represented is 2≤c * ≤10.
[0014] In a fourth aspect, in any one of the first to third aspects, 80≤L*≤97.
[0015] In a fifth aspect, in any one of the first to fourth aspects, the crystal structure of the electrolyte powder further includes Mg and Sr.
[0016] A sixth aspect is a sheet including the electrolyte powder according to any one of the first to fifth aspects.
[0017] A seventh aspect is an electrochemical device including the electrolyte powder according to any one of the first to fifth aspects.
[0018] An eighth aspect is a power storage device including a plurality of electrode layers and a separator separating the plurality of electrode layers, wherein at least one of the plurality of electrode layers and the separator contains the electrolyte powder according to any one of the first to fifth aspects.
[0019] The ninth aspect is a power storage device, comprising a plurality of electrode layers including a current collecting layer and a separator separating the plurality of electrode layers, wherein the power storage device comprises a protective layer arranged between the electrode layer and the separator or arranged on the current collecting layer, and the protective layer comprises an electrolyte powder of any one of the first to fifth aspects.
[0020] Effects of the Invention
[0021] According to the electrolyte powder, sheet, electrochemical element and power storage device of the present invention, quality management can be simplified. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a cross-sectional view of the electrochemical device according to the first embodiment.
[0023] Figure 2 A diagram schematically showing a garnet-type crystal structure.
[0024] Figure 3 It is a cross-sectional view of the electrochemical device according to the second embodiment.
[0025] Figure 4 It is a cross-sectional view of an electrochemical device according to a third embodiment.
[0026] Figure 5 It is a graph showing the correlation between the specific surface area of the electrolyte powder and b*.
[0027] Figure 6 It is a graph showing the correlation between the specific surface area of the electrolyte powder and c*. DETAILED DESCRIPTION
[0028] Hereinafter, preferred embodiments of the present invention will be described with reference to the drawings. Figure 1Schematic cross-sectional view of an electrochemical element 10 of one embodiment. The electrochemical element 10 of this embodiment is a lithium ion solid battery (electricity storage device) in which the power generation element is composed of a solid. The power generation element is composed of a solid means that the skeleton of the power generation element is composed of a solid, including a form in which a liquid is impregnated in the skeleton.
[0029] The electrochemical element 10 includes, in order, a positive electrode layer 11, an electrolyte layer 14, and a negative electrode layer 15. The positive electrode layer 11, the electrolyte layer 14, and the negative electrode layer 15 are housed in a case (not shown).
[0030] The positive electrode layer 11 is formed by laminating a collector layer 12 and an active material layer 13. The collector layer 12 is a conductive member. Examples of the material of the collector layer 12 include metals selected from Ni, Ti, Fe and Al, alloys containing two or more of these elements, stainless steel, and carbon materials.
[0031] Active material layer 13 includes electrolyte powder 18 and active material 19. Active material layer 13 may contain a conductive additive to reduce the resistance of active material layer 13. Examples of the conductive additive include carbon black, acetylene black, Ketjen black, carbon fiber, Ni, Pt, and Ag.
[0032] Examples of active material 19 include metal oxides containing transition metals, sulfur-based active materials, and organic active materials. Examples of metal oxides containing transition metals include metal oxides containing one or more elements selected from Mn, Co, Ni, Fe, Cr, and V, and Li. Examples of metal oxides containing transition metals include LiCoO2, LiNi 0.8 Co 0.15 Al 0.05 O2, LiMn2O4, LiNiVO4, LiNi 0.5 Mn 1.5 O2、LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2 and LiFePO4.
[0033] In order to suppress the reaction between the active material 19 and the electrolyte powder 18, a coating layer may be provided on the surface of the active material 19. Examples of the coating layer include Al2O3, ZrO2, LiNbO3, Li4Ti5O 12 , LiTaO3, LiNbO3, LiAlO2, Li2ZrO3, Li2WO4, Li2TiO3, Li2B4O7, Li3PO4 and Li2MoO4.
[0034] Examples of sulfur-based active materials include S, TiS2, NiS, FeS2, Li2S, MoS3, and sulfur-carbon complexes. Examples of organic-based active materials include free radical compounds represented by 2,2,6,6-tetramethylpiperidinyloxy-4-yl methacrylate and polytetramethylpiperidinyloxyvinyl ether, quinone compounds, axialene compounds, tetracyanobenzoquinodimethane, and phenazine oxide.
[0035] The electrolyte layer 14 includes an electrolyte powder 18. The electrolyte layer 14 may contain an electrolyte solution obtained by dissolving an electrolyte salt in a solvent, and a binder. The solvent of the electrolyte solution is not particularly limited as long as it is a solvent that dissolves the electrolyte salt. Examples of the solvent include: carbonates, aliphatic carboxylates, phosphates, γ-lactones, ethers, nitriles, cyclopentane, dimethyl sulfoxide, fluorinated solvents, and ionic liquids. It may be a mixture thereof. The electrolyte layer 14 of this embodiment is equivalent to a separator. The separator refers to a component that separates the positive electrode layer 11 and the negative electrode layer 15 and electrically insulates them from each other.
[0036] The binder is not particularly limited as long as it is a material that binds the electrolyte powder 18. Examples of the binder include fluororesins, polyolefins, polyimides, polyvinyl pyrrolidone, polyvinyl alcohol, cellulose ethers, and rubber polymers such as styrene-butadiene rubber. Examples of the fluororesins include vinylidene fluoride polymers, polychlorotrifluoroethylene, polyvinyl fluoride, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymers, tetrafluoroethylene-hexafluoropropylene copolymers, ethylene tetrafluoroethylene copolymers, and ethylene-chlorotrifluoroethylene copolymers.
[0037] The negative electrode layer 15 is formed by laminating a collector layer 16 and an active material layer 17. The collector layer 16 is a conductive member. Examples of the material of the collector layer 16 include metals selected from Ni, Ti, Fe, Cu and Si, alloys containing two or more of these elements, stainless steel, and carbon materials.
[0038] The active material layer 17 includes an electrolyte powder 18 and an active material 20. In order to reduce the resistance of the active material layer 17, a conductive additive may be contained in the active material layer 17. Examples of the conductive additive include carbon black, acetylene black, Ketjen black, carbon fiber, Ni, Pt, and Ag. Examples of the active material 20 include Li, Li-Al alloy, Li4Ti5O 12 , graphite, In, Si, Si—Li alloy, and SiO. Similar to the electrolyte layer 14 , the active material layers 13 and 17 may contain an electrolyte solution and a binder.
[0039] The electrochemical element 10 is manufactured, for example, in the following manner. For example, the electrochemical element 10 includes an electrolyte solution and a binder. An organic solvent in which a lithium salt is dissolved is mixed with the electrolyte powder 18, and the obtained mixture is mixed with a solution in which the binder is dissolved in the solvent to prepare a slurry. After being formed into a tape, it is dried to obtain a green sheet (electrolyte sheet) for the electrolyte layer 14.
[0040] An organic solvent in which a lithium salt is dissolved is mixed with electrolyte powder 18, the obtained mixture is mixed with active material 19, and further mixed with a solution obtained by dissolving a binder in a solvent to prepare a slurry. After being formed into a tape on the collector layer 12, it is dried to obtain a green sheet (positive electrode sheet) for the positive electrode layer 11.
[0041] An organic solvent in which a lithium salt is dissolved is mixed with electrolyte powder 18, the obtained mixture is mixed with active material 20, and further mixed with a solution obtained by dissolving a binder in a solvent to prepare slurry. After being formed into a tape on the collector layer 16, it is dried to obtain a green sheet (negative electrode sheet) for the negative electrode layer 15.
[0042] The electrolyte sheet, the positive electrode sheet and the negative electrode sheet are cut into predetermined shapes, respectively, and then stacked in the order of the positive electrode sheet, the electrolyte sheet and the negative electrode sheet, and crimped to each other to form an integrated whole. Terminals (not shown) are connected to the collector layers 12 and 16, respectively, and a housing (not shown) is sealed to obtain an electrochemical element 10 comprising a positive electrode layer 11, an electrolyte layer 14 and a negative electrode layer 15. It should be noted that, of course, at least one of the positive electrode layer 11, the electrolyte layer 14 and the negative electrode layer 15 may not contain at least one of an electrolyte and a binder.
[0043] The electrolyte powder 18 is a composite oxide having a garnet-type crystal structure or a garnet-like crystal structure containing Li, Zr and La. The garnet-type crystal structure is represented by the general formula C3A2B3O 12 express.
[0044] Figure 2A diagram schematically showing a garnet-type crystal structure. In the garnet-type crystal structure, the C site Sc is coordinated with the oxygen atom Oa in a dodecahedral manner, the A site Sa is coordinated with the oxygen atom Oa in an octahedral manner, and the B site Sb is coordinated with the oxygen atom Oa in a tetrahedral manner. In the electrolyte powder 18, in a conventional garnet-type crystal structure, Li may exist in a portion that is coordinated with the oxygen atom Oa in an octahedral manner and becomes a void V. The void V is, for example, a portion sandwiched by the B site Sb1 and the B site Sb2. The Li present in the void V is coordinated with the oxygen atom Oa constituting an octahedron in an octahedral manner, and the octahedron includes a tetrahedral face Fb1 forming the B site Sb1 and a tetrahedral face Fb2 forming the B site Sb2. For example, for Li7La3Zr2O having a garnet-type crystal structure 12 , La can occupy the C site Sc, Zr can occupy the A site Sa, and Li can occupy the B site Sb and the gap V.
[0045] The garnet crystal structure can be identified by X-ray diffraction. The garnet crystal structure has the same X-ray diffraction file No. 422259 (Li7La3Zr2O 12 ) is similar to the XRD pattern of No. 422259. Compared with No. 422259, the types of constituent elements and Li concentration of electrolyte powder 18 are sometimes different, so the diffraction angle and intensity ratio are sometimes different. The typical crystal structure of this type is cubic (space group Ia-3d (- is an overline indicating a rotation operation), JCPDS: 84-1753).
[0046] As the electrolyte powder 18, Li7La3Zr2O 12 For electrolyte powder 18, Li7La3Zr2O can be replaced by other elements. 12 The present invention can be used as a part of the constituent elements of the present invention, and other elements can be added in a trace amount without replacing the constituent elements. As other elements, at least one element selected from the group consisting of Mg, Al, Si, Ca, Ti, V, Ga, Sr, Y, Nb, Sn, Sb, Ba, Hf, Ta, W, Bi, Rb and lanthanide elements (excluding La) can be exemplified.
[0047] Examples of the electrolyte powder 18 include Li6La3Zr 1.5 W 0.5 O 12 , Li 6.15 Ln3Z 1.75 Ta 0.25 Al 0.2 O 12 , Li 6.15 Ln3Z 1.75 Ta 0.25 Ga0.2 O 12 , Li 6.25 La3Zr2Ga 0.25 O 12 , Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 , Li 6.5 Ln3Z 1.75 Te 0.25 O 12 , Li 6.75 Ln3Z 1.75 Nb 0.25 O 12 , Li 6.9 Ln3Z 1.675 Ta 0.289 Bi 0.036 O 12 , Li 6.46 Ga 0.23 Ln3Z 1.85 Y 0.15 O 12 , Li 6.8 La 2.95 Ca 0.05 Zr 1.75 Nb 0.25 O 12 , Li 7.05 La 3.00 Zr 1.95 G 0.05 O 12 , Li 6.20 Ba 0.30 La 2.95 R 0.05 Zr2O 12 .
[0048] The electrolyte powder 18 particularly preferably contains at least one of Mg and element A (A is at least one element selected from the group consisting of Ca, Sr and Ba) and the molar ratio of each element satisfies all of the following (1) to (3), or contains both Mg and element A and the molar ratio of each element satisfies all of the following (4) to (6). In order to improve the ion conductivity of the electrolyte powder 18, element A is preferably Sr.
[0049] (1) 1.33 ≤ Li / (La+A) ≤ 3
[0050] (2) 0≤Mg / (La+A)≤0.5
[0051] (3)0≤A / (La+A)≤0.67
[0052] (4) 2.0≤Li / (La+A)≤2.5
[0053] (5) 0.01≤Mg / (La+A)≤0.14
[0054] (6) 0.04 ≤ A / (La+A) ≤ 0.17
[0055] The electrolyte powder 18 utilizes the CIE 1976L chromatic algebra including quantities related to each of brightness, saturation, and hue. * a * b * The color coordinates of the color space are determined. CIE 1976L * a * b * The color space is recommended by CIE (International Commission on Illumination) in 1976 by plotting L on orthogonal coordinates. * 、a * 、b * The resulting three-dimensional color space is roughly equal. CIE 1976L * a * b * The color space is specified by JIS Z8781-4:2013.
[0056] In CIE 1976L * a * b * In color space, L * represents brightness, and chromaticity showing hue and saturation is represented by a* and b*. a* and b* represent the direction of color, a * Indicates the red direction, -a * Indicates the green direction, b * Indicates yellow direction, -b * Indicates the blue direction. The larger the value, the brighter the color, and the closer to the origin, the darker the color. Saturation c * Use {(a * ) 2 +(b * ) 2} 1 / 2 (a * and b * L*, a*, and b* can be measured using a spectrophotometer CM-5 (Konica Minolta, Inc.).
[0057] The specific surface area (m2) of the electrolyte powder 18 having a garnet crystal structure containing Li, Zr and La obtained by a gas adsorption method (BET method) is 2 / g) and b *There is a positive correlation between the values of L*, a*, and b*. Each value of L*, a*, and b* is not a property that can be completely controlled independently, but when b* ≥ 2, electrolyte powders with small specific surface areas can be excluded. Compared with the specific surface area obtained by gas adsorption method, the b* of electrolyte powder 18 is more * It is easier to detect impurities, so quality management can be simplified. * The maximum value is 60.
[0058] The specific surface area of the electrolyte powder is related to b * The reason for the positive correlation is unclear, but when a large amount of energy is applied to pulverize the electrolyte powder, the yellowness of the powder increases and becomes brighter. This is because the particle size becomes smaller due to pulverization, and a layer with destroyed crystallinity is generated on the surface of the powder. Therefore, it is inferred that as the specific surface area of the electrolyte powder 18 increases, b * Get bigger.
[0059] The electrolyte layer 14 and the active material layers 13 and 17 may contain one or more other solid electrolytes in addition to the electrolyte powder 18. Other solid electrolytes include crystalline and amorphous oxide solid electrolytes such as perovskite, NASICON, and LISICON, and hydride solid electrolytes.
[0060] Examples of the perovskite-type solid electrolyte include oxides containing at least Li, Ti, and La, such as La 2 / 3- X Li 3X As NASICON-type solid electrolytes, oxides containing at least Li, M (M is one or more elements selected from Ti, Zr and Ge) and P, such as Li(Al,Ti)2(PO4)3 and Li(Al,Ge)2(PO4)3, can be cited. As LISICON-type solid electrolytes, Li 14 Zn(GeO4)4. As hydride-based solid electrolytes, there can be exemplified solid electrolytes that are hydrides of alkali metals or alkaline earth metals and contain at least one of the 13th group elements (e.g., B, Al, Ga, In, Ta) of the 18th group periodic table. For example, LiBH4 and LiAlH4 can be cited.
[0061] Reference Figure 3 The second embodiment is described. In the first embodiment, the case where the electrolyte powder 18 is used in a secondary battery whose power generation element is composed of a solid is described. In the second embodiment, the case where the electrolyte powder 18 is used in a liquid lithium ion battery using an organic solvent as an electrolyte is described. The same reference numerals are given to the same parts as those described in the first embodiment, and the following description is omitted. Figure 3 It is a cross-sectional view of an electrochemical element 21 (electricity storage device) according to the second embodiment.
[0062] The electrochemical element 21 includes a positive electrode layer 11, a separator 22 and a negative electrode layer 15 in sequence. They are contained in a housing (not shown). The separator 22 is durable to the active materials 19, 20 and the electrolyte contained in the positive electrode layer 11 and the negative electrode layer 15, and is composed of a porous body that allows lithium ions to pass but does not have electronic conductivity. As the separator 22, non-woven fabrics and porous films composed of cellulose, polypropylene, polyethylene, etc. can be exemplified. The electrolyte is the same as the electrolyte described in the first embodiment, so the description is omitted.
[0063] Since the electrochemical element 21 of the second embodiment contains the electrolyte powder 18 in the positive electrode layer 11 and the negative electrode layer 15 , the quality management of the electrolyte powder 18 can be simplified similarly to the power storage device 11 of the first embodiment.
[0064] Reference Figure 4 The third embodiment is described. In the first and second embodiments, the case where the electrolyte powder 18 is included in the positive electrode layer 11, the electrolyte layer 14, and the negative electrode layer 15 is described. In the third embodiment, the case where the electrolyte powder 18 is included in the protective layers 25 and 28 is described. The same reference numerals are given to the same parts as those described in the first and second embodiments, and the following description is omitted. Figure 4 It is a cross-sectional view of an electrochemical element 23 (electricity storage device) according to the third embodiment.
[0065] The electrochemical element 23 includes a positive electrode layer 24, a separator 22, and a negative electrode layer 26 in this order. These are housed in a case (not shown). The electrochemical element 23 is a liquid-type lithium-ion battery using an organic solvent as an electrolyte.
[0066] The positive electrode layer 24 is formed by laminating the current collecting layer 12 and the active material layer 25. The active material layer 25 contains the active material 19. In order to reduce the resistance of the active material layer 25, the active material layer 25 may contain a conductive additive such as carbon black, acetylene black, Ketjen black, carbon fiber, Ni, Pt, and Ag.
[0067] The protective layer 26 is disposed between the separator 22 and the negative electrode layer 27 . The protective layer 26 contains the electrolyte powder 18 .
[0068] The negative electrode layer 27 is formed by stacking an active material layer 28, a protective layer 29, and a current collecting layer 16 in this order. The active material layer 28 is composed of, for example, Li, Li-Al alloy, Li-Sn alloy, Li-Si alloy, Li-Mg alloy, Li-Si alloy, or Si-Li alloy. The protective layer 29 contains electrolyte powder 18. The protective layers 26 and 29 are configured by stacking sheets, coating the separator 22, the current collecting layer 16, etc.
[0069] Since the electrolyte powder 18 having a garnet-type crystal structure containing Li, La, Zr, and O has resistance to reduction of the metal lithium of the active material layer 28, the operation stability of the electrochemical element 23 is increased. In addition, the protective layer 26 interposed between the active material layer 28 and the separator 22 suppresses short circuits caused by dendrite growth of the metal lithium. The protective layer 29 interposed between the active material layer 28 and the collector layer 16 suppresses deterioration of the collector layer 16.
[0070] Example
[0071] The present invention will be described in further detail by way of examples, but the present invention is not limited to these examples.
[0072] (Example 1)
[0073] Weigh Li2CO3, MgO, La(OH)3, SrCO3, ZrO2 to make Li 6.95 Mg 0.15 La 2.75 Sr 0.25 Zr 2.0 O 12 . Considering the volatilization of Li during firing, Li2CO3 is in excess of about 15 mol% in terms of element conversion. The weighed raw materials and ethanol are put into a nylon can together with zirconium oxide balls, and crushed and mixed for 15 hours using a ball mill. The slurry taken out of the can is dried and then fired on a MgO plate at 1100°C for 15 hours. The fired powder is crushed, placed in a MgO sleeve, and further fired at 1100°C for 4 hours. The fired powder is crushed in a glove box with an argon atmosphere to obtain an electrolyte powder (hereinafter referred to as "LLZ").
[0074] The crystal structure of LLZ was confirmed to be garnet-type by powder X-ray diffraction. The median diameter (D50) of the particle size distribution of LLZ measured by laser diffraction / scattering was 74 μm.
[0075] Using a dry jet mill (Aisin Nano Technologies Co., Ltd., Nano Jetmizer (registered trademark) NJ-50 model), the nozzle initial pressure was set to 2.0 MPa, and LLZ was passed through the jet mill once at a processing rate of 960 g / hour under a nitrogen atmosphere to pulverize LLZ. Thus, the electrolyte powder of Example 1 was obtained.
[0076] (Example 2)
[0077] The electrolyte powder of Example 2 was obtained in the same manner as in Example 1 except that the conditions for the primary pulverization were set to a nozzle initial pressure of 2.0 MPa, the processing amount was set to 960 g / hour, and LLZ was pulverized by passing through the jet mill a total of three times.
[0078] (Example 3)
[0079] Electrolyte powder of Example 3 was obtained in the same manner as in Example 1 except that the conditions for the primary pulverization were set to a nozzle initial pressure of 2.0 MPa, the processing amount was set to 480 g / hour, and LLZ was pulverized by passing through the jet mill a total of three times.
[0080] (Example 4)
[0081] Instead of using a jet mill for pulverization, a planetary ball mill (Pulverisette-6, Fritsh: volume 250 cm 3 100 g of LLZ and 125 mL of Fluorinert (registered trademark) were placed in a zirconia container (a zirconia container with a diameter of 4 mm, zirconia balls with a diameter of 4 mm), wet-pulverized for 5 hours at 400 rpm in an argon atmosphere, and then dried. Except for this, the same operation as in Example 1 was carried out to obtain the electrolyte powder of Example 4.
[0082] (Example 5)
[0083] In addition to becoming Li 6.75 Mg 0.15 La 2.75 Sr 0.25 Zr 2.0 O 12 The electrolyte powder of Example 5 was obtained in the same manner as in Example 1 except that the electrolyte powder (hereinafter referred to as "LLZ-1") was prepared in the manner of . The crystal structure of LLZ-1 was confirmed to be garnet type by powder X-ray diffraction.
[0084] (Example 6)
[0085] In addition to becoming Li 6.55 Mg 0.15 La2.75 Sr 0.25 Zr 2.0 O 12 The electrolyte powder of Example 6 was obtained in the same manner as in Example 1 except that the electrolyte powder (hereinafter referred to as "LLZ-2") was prepared in the manner of . The crystal structure of LLZ-2 was confirmed to be garnet type by powder X-ray diffraction.
[0086] (Example 7)
[0087] In addition to becoming Li 6.95 Mg 0.1 La 2.75 Sr 0.2 Zr 2.0 O 12 The electrolyte powder of Example 7 was obtained in the same manner as in Example 1 except that the electrolyte powder (hereinafter referred to as "LLZ-3") was prepared in the manner of . The crystal structure of LLZ-3 was confirmed to be garnet type by powder X-ray diffraction.
[0088] (Example 8)
[0089] In addition to becoming Li 6.95 Mg 0.2 La 2.75 Sr 0.4 Zr 2.0 O 12 The electrolyte powder of Example 8 was obtained in the same manner as in Example 1 except that the electrolyte powder (hereinafter referred to as "LLZ-4") was prepared in the manner of . The crystal structure of LLZ-4 was confirmed to be garnet type by powder X-ray diffraction.
[0090] (Comparative Example 1)
[0091] Electrolyte powder of Comparative Example 1 was obtained in the same manner as in Example 1 except that LLZ was coarsely pulverized using a mortar for about 1 minute instead of pulverizing using a jet mill.
[0092] (Comparative Example 2)
[0093] Electrolyte powder of Comparative Example 2 was obtained in the same manner as in Example 1, except that LLZ was pulverized in a mortar for 30 minutes instead of pulverizing with a jet mill.
[0094] (Comparative Example 3)
[0095] Li with a garnet crystal structure 6.6 La3Ta 0.4 Zr 1.6 O 12Place in a planetary ball mill (Pulverisette-6, Fritsh Company: volume 250cm 3 A zirconia container (with a diameter of 4 mm, zirconia balls) was placed, and 100 g of LLZ and 125 mL of Fluorinert (registered trademark) were added, and wet pulverized for 1 hour under an argon atmosphere at 200 rpm, and then dried to obtain the electrolyte powder of Comparative Example 3.
[0096] (Color determination)
[0097] The colors of the electrolyte powders of Examples 1 to 8 and Comparative Examples 1 to 3 were measured using a spectrophotometer CM-5 (manufactured by Konica Minolta, Inc.) to obtain CIE 1976L * a * b * L*, a*, b* in the color space. Further substitute a* and b* into the saturation c * ={(a * ) 2 +(b * ) 2} 1 / 2 In the formula, the saturation c of the electrolyte powder of Examples 1-8 and Comparative Examples 1-3 is obtained. * .
[0098] (Determination of particle size distribution and specific surface area)
[0099] The median diameter (D50) of the particle size distribution of the electrolyte powders of Examples 1-8 and Comparative Examples 1-3 was measured by laser diffraction / scattering method. In addition, the specific surface area of the electrolyte powders of Examples 1-8 and Comparative Examples 1-3 was measured in accordance with JIS R1626:1996.
[0100] (Evaluation of bonding properties)
[0101] Propylene carbonate in which polyvinylidene fluoride is dissolved is mixed in the electrolyte powders of Examples 1-8 and Comparative Examples 1-3, respectively, and then a planetary mixer is used to make a slurry. The ratio of the adhesive mixed in the electrolyte powder is set to 80% by mass relative to the total amount of the electrolyte powder and the adhesive. The slurry is applied to a copper foil (thickness 20 μm) with a thickness of 50 μm using an applicator, and then dried under reduced pressure at 80°C for 1 hour to obtain various sheets having a coating layer formed on the copper foil. The sheet is cut into a size of 50 mm long and 50 mm wide, and in a state where the coating layers of the two sheets are in close contact with each other, a roller press heated to 60°C is used to press (50 MPa) to obtain a laminate.
[0102] A peeling stress was applied to one end of the copper foil of the laminate at an angle of 90°. If the sheet was peeled off with a force of 0.01 N or more, it was judged that the bonding was good, and if the sheet was peeled off with a force of less than 0.01 N, it was judged that the bonding was poor. In addition, the resistance value of the laminate was measured using the AC impedance method, and a resistance value of less than 45 Ω / cm 2 The case of 45Ω / cm was judged to be good bonding, and the resistance value was 45Ω / cm 2 The above cases are judged as poor bonding.
[0103] The electrolyte powders in Examples 1-8 and Comparative Examples 1-3 were * 、a * 、b * 、c * The evaluation of D50, specific surface area, and bonding properties is shown in Table 1. For the evaluation of bonding properties, the peel strength was 0.01 N or more and the resistance was less than 45 Ω / cm. 2 The evaluation was good, and the peel strength was less than 0.01N or the resistance was 45Ω / cm 2 As shown in Table 1, the bonding properties of Examples 1-8 were good, but the bonding properties of Comparative Examples 1-3 were poor.
[0104]
[0105] Figure 5 It is a graph showing the correlation between the specific surface area and b* of the electrolyte powders of Examples 1-8 and Comparative Examples 1-3. Figure 6 Graph showing the correlation between the specific surface area and c* of the electrolyte powders of Examples 1-8 and Comparative Examples 1-3. Figure 5 and Figure 6 In the figure, the black circles are examples and the hollow circles are comparative examples.
[0106] like Figure 5 As shown in Table 1, b * The evaluation of the bonding properties of the electrolyte powders of Examples 1 to 8 with a value of 2 or more was good. * The specific surface area of the electrolyte powder of Examples 1-8 is greater than 0.6 m 2 / g (Comparative Example 3). Therefore, when b * When b is greater than 2, electrolyte powder with a small specific surface area can be excluded. The specific surface area of the electrolyte powder affects various properties of the electrolyte powder, such as ion conductivity, interface resistance, viscosity of the slurry containing the electrolyte powder, and bonding properties of the sheet containing the electrolyte powder. Compared with the specific surface area of the electrolyte powder obtained by the gas adsorption method, the specific surface area of the electrolyte powder is more easily determined by measuring the specific surface area of the electrolyte powder. * Therefore, the quality management of the electrolyte powder can be simplified.
[0107] like Figure 5 As shown in Table 1, the solid electrolytes (Examples 1-8) containing Li, Zr, La, Mg and Sr have a * ≥0, and in the specific surface area and b * There is a strong positive correlation between them, so it can improve the * It is the accuracy of quality management as an indicator. It should be noted that from the perspective of detecting the mixing of impurities, a * The maximum value is 60.
[0108] like Figure 6 As shown in the figure, the specific surface area of the solid electrolyte is related to c * The specific surface area and b * There is also a positive correlation between * When it is 2 or more, electrolyte powder with a small specific surface area can be excluded. * Including b * In addition, it also includes a showing the red direction and the green direction * , so when c * When it is 10 or less, powder mixed with red impurities and green impurities and measurement errors can be eliminated. * The electrolyte powders of Examples 1 to 8 with a specific surface area of ≤10 can exclude powders with a small specific surface area and powders mixed with impurities.
[0109] Brightness L * It is preferably 80 or more. This is because it can exclude powder mixed with black impurities. * It is preferably 97 or less. This is because measurement errors can be eliminated. According to the electrolyte powders of Examples 1-8 with 80≤L*≤97, powders mixed with impurities can be eliminated.
[0110] As mentioned above, although this invention was demonstrated based on embodiment, this invention is not limited to the said embodiment at all, It can be easily guessed that various improvements and modifications can be made within the range which does not deviate from the summary of this invention.
[0111] In the embodiment, as the electrochemical element 10, an electrochemical element having a positive electrode layer 11 having an active material layer 13 provided on one side of a current collector layer 12 and a negative electrode layer 15 having an active material layer 17 provided on one side of a current collector layer 16 is described, but it is not necessarily limited to this. For example, in an electrochemical element having an electrode layer (so-called bipolar electrode) having active material layers 13 and 17 provided on both sides of a current collector layer 12, each element of the embodiment can of course be applied. If the bipolar electrodes and the electrolyte layer 14 are alternately stacked and housed in a housing (not shown), an electrochemical element of a so-called bipolar structure can be obtained.
[0112] In the first embodiment, the active material layers 13 and 17 and the electrolyte layer 14 both contain the electrolyte powder 18 , but the present invention is not necessarily limited thereto. The electrochemical element only needs to contain the electrolyte powder 18 at least one of the active material layers 13 and 17 and the electrolyte layer 14 .
[0113] In the second embodiment, the case where both active material layers 13 and 17 contain electrolyte powder 18 is described, but the present invention is not necessarily limited to this. The electrochemical element 21 only needs to have at least one of the active material layers 13 and 17 contain electrolyte powder 18 .
[0114] In the third embodiment, the protective layer 26 is provided between the active material layer 28 and the separator 22 and the protective layer 29 is provided between the current collecting layer 16 and the active material layer 28 , but the present invention is not necessarily limited thereto. Of course, either the protective layer 26 or 29 may be omitted.
[0115] In the embodiment, the electrolyte powder 18 is described by taking the electrochemical element 10 including a lithium ion battery as an example, but is not necessarily limited thereto. Other electrochemical elements including the electrolyte powder 18 include lithium ion capacitors, lithium sulfur batteries, lithium oxygen batteries, and lithium air batteries.
[0116] Explanation of symbols
[0117] 10, 21, 23 Electrochemical elements (electricity storage devices)
[0118] 11 Positive electrode layer (sheet, electrode layer)
[0119] 14Electrolyte layer (sheet, diaphragm)
[0120] 15 negative electrode layer (sheet, electrode layer)
[0121] 16 collector layer
[0122] 18 Electrolyte powder
[0123] 22 Diaphragm
[0124] 26, 29 protection layer
[0125] 27 negative electrode layer (electrode layer)
Claims
1. An electrolyte powder having a garnet-type crystal structure containing Li, Zr and La, wherein: In the color coordinates of the CIE 1976 L*a*b* color space, b*≥2.
2. The electrolyte powder according to claim 1, wherein In the color coordinates, a * ≥0.
3. The electrolyte powder according to claim 1 or 2, wherein In the color coordinates, c*={(a * ) 2 +(b * ) 2 } 1 / 2 The saturation represented is 2≤c * ≤10.
4. The electrolyte powder according to claim 1 or 2, wherein In the color coordinates, 80≤L*≤97.
5. The electrolyte powder according to claim 1 or 2, wherein The crystal structure also contains Mg and Sr. 6 . A sheet comprising the electrolyte powder according to claim 1 or 2 . 7 . An electrochemical element, comprising the electrolyte powder according to claim 1 .
8. A power storage device comprising a plurality of electrode layers and a separator separating the plurality of electrode layers, At least one of the plurality of electrode layers and the separator includes the electrolyte powder of claim 1 .
9. A power storage device comprising a plurality of electrode layers including a power collecting layer and a separator separating the plurality of electrode layers, wherein: The power storage device includes a protective layer provided between the electrode layer and the separator or provided on the power collecting layer. The protective layer comprises the electrolyte powder of claim 1 .
